2010
DOI: 10.1074/jbc.m110.140350
|View full text |Cite
|
Sign up to set email alerts
|

Anti-apoptotic Protein BCL2 Down-regulates DNA End Joining in Cancer Cells

Abstract: Cancer cells are often associated with secondary chromosomal rearrangements, such as deletions, inversions, and translocations, which could be the consequence of unrepaired/misrepaired DNA double strand breaks (DSBs). Nonhomologous DNA end joining is one of the most common pathways to repair DSBs in higher eukaryotes. By using oligomeric DNA substrates mimicking various endogenous DSBs in a cell-free system, we studied end joining (EJ) in different cancer cell lines. We found that the efficiency of EJ varies a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 61 publications
0
63
2
Order By: Relevance
“…Majority of the joined products observed by us were consistent with those shown in earlier reports. 15,39,50,53,54 In contrast to some of the earlier reports, we also observed intramolecular circularization. 42,[53][54][55] Comparison of NHEJ activities showed that the joining of DSBs was highest in 14.5-day cephalon, irrespective of the nature of DSBs.…”
Section: 5-day Cephalon Possess Robust Nhej Activitycontrasting
confidence: 82%
See 2 more Smart Citations
“…Majority of the joined products observed by us were consistent with those shown in earlier reports. 15,39,50,53,54 In contrast to some of the earlier reports, we also observed intramolecular circularization. 42,[53][54][55] Comparison of NHEJ activities showed that the joining of DSBs was highest in 14.5-day cephalon, irrespective of the nature of DSBs.…”
Section: 5-day Cephalon Possess Robust Nhej Activitycontrasting
confidence: 82%
“…[42][43][44][45][46] Besides the efficiency of repair, the mechanism of regulation of NHEJ, the regulation of their proteins, and various protein-protein interactions were also studied using such a system. 15,39,[43][44][45][47][48][49][50][51][52][53][54] However, it is not clear whether the end-joining events observed in our studies correspond to in vivo NHEJ events, although the various lines of experimental evidence suggest an in vivo mechanistic correlation. Moreover, we could also correlate the expression of proteins detected by immunoblotting at different developmental stages to the immunofluorescence observed at the intracellular level (see the text below).…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…Quantification was performed using Multi Gauge V 3.0, as described earlier. 55,56 Electrophoretic mobility shift assay Radiolabeled oligomeric DNA substrates containing the standard 12-RSS and 6-nt bubbles were incubated with RAGs in a buffer containing 25 mM 4-morpholinepropanesulfonic acid (pH 7.0), 30 mM KCl, 30 mM potassium glutamate, and 5 mM MgCl 2 . A 45-bp double-stranded oligomer (0.1 Ī¼M) was used as nonspecific DNA.…”
Section: Rag Expression and Purificationmentioning
confidence: 99%
“…Bands of interest resulting from independent transfections were cut out from the dried gel, and removal of the bands was confirmed by scanning. The DNA from the bands was eluted in 500 mM NaCl, 10 mM Tris, and 1 mM EDTA and purified (39). The recombinant was then PCR-amplified and ligated to a TA vector (Invitrogen), and positive clones were sequenced (SciGenom).…”
Section: Electrophoretic Mobility Shift Assay (Emsa)-the [ā„-mentioning
confidence: 99%